2015
DOI: 10.3390/ijms160511574
|View full text |Cite
|
Sign up to set email alerts
|

Vasa Vasorum in Atherosclerosis and Clinical Significance

Abstract: Atherosclerosis is a chronic inflammatory disease that leads to several acute cardiovascular complications with poor prognosis. For decades, the role of the adventitial vasa vasorum (VV) in the initiation and progression of atherosclerosis has received broad attention. The presence of VV neovascularization precedes the apparent symptoms of clinical atherosclerosis. VV also mediates inflammatory cell infiltration, intimal thickening, intraplaque hemorrhage, and subsequent atherothrombosis that results in stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
91
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 184 publications
(197 reference statements)
1
91
0
1
Order By: Relevance
“…[25][26][27] In contrast, the progression of atherosclerotic plaque 28 and the presence of an oxygeninsufficient microenvironment, the inner layers may provide an inside-to-outside signal, similar to hypoxic conditions, resulting in EAT accumulation. 29 This may be supported by our previous observation that pro-inflammatory cytokine profiles are more prominently enhanced in locations where severe atherosclerosis is observed. 1,30…”
Section: Discussionsupporting
confidence: 78%
“…[25][26][27] In contrast, the progression of atherosclerotic plaque 28 and the presence of an oxygeninsufficient microenvironment, the inner layers may provide an inside-to-outside signal, similar to hypoxic conditions, resulting in EAT accumulation. 29 This may be supported by our previous observation that pro-inflammatory cytokine profiles are more prominently enhanced in locations where severe atherosclerosis is observed. 1,30…”
Section: Discussionsupporting
confidence: 78%
“…The vasa vasorum has been thought to be not only a function of intimal thickness but also involved in atherosclerotic progression [26]. In animal models, an increased vasa vasorum was associated with intimal thickening and endothelial dysfunction, and these effects were blocked with angiogenic inhibitors [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the initiation phase using a rabbit model fed an atherogenic diet for 3 weeks showed that local delivery of bevacizumab (a monoclonal antibody against VEGF‐A) inhibited plaque angiogenesis, resulting in smaller atherosclerotic plaques . Despite their clinical relevance, there are few studies of anti‐angiogenic therapy on the progression and complication stages and inappropriate anti‐angiogenic therapy at these two stages can potentially cause hypoxia and induce endothelial apoptosis, resulting in the loss of integrity of the endothelial vessel lining (bleeding) . This observation raised concerns regarding the importance of vascular‐normalization therapy in atherosclerotic plaque .…”
Section: Introductionmentioning
confidence: 99%